Octenilsuccinato alumínico de almidón de quinua - grado cosmético- y su certificación bajo la denominación de "ingrediente natural" (2014)
The process for evaluating/obtain/certify Aluminum Quinoa Starch Octenylsuccinate (AQSO) - cosmetic grade, with the designation of natural ingredient. The process consisted of two phases: a) reaction of esterification, under "Similar method": parameters: reaction time 4 hours, reaction temperature of 35 "C, reaction pH of 8.5 and concentration of starch of 35 w/w, b) "Sirni Lb' method corresponds to the reaction second substitution based on Cosmetic Ingredient Review Expert Panel, which uses aluminium sulphate to 2; requirement in cosmetics.